Implementation Of Direct Learning Model In Group To Improve Mathematics Achievement In Fifth Grade Students At Sdn 06 Perawang Barat In Academic Year 2012/2013 - Maiharti Hadijah (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Teacher has a very important role in creating an exciting and enjoyable learning environment in math lessons.Learning atmosphere is not exciting and fun for students usually to create learning activities that are less harmonious.As in SD 06 Perawang Barat is still low learning achievement of mathematics students, especially VD class with the number of students 32 people.Based on the mathematical repetition value of grade VD students contained in table 1 can be concluded that most students have not reached the established KKM that is 60 in 2012/2013 Another effort that teachers do is to provide practice questions (PR). Then the teacher also repeats the material that the students have not understood. But the effort made by the teacher has not achieved the expected result; low student learning achievement to mathematics is a material for researchers, that the need for mathematics learning that can improve the results of learning mathematics. The formulation of the problem in this study is whether the application of direct learning model in groups can improve student achievement on the subject matter of the fractional matter in the VD SDN 06 Perawang Barat class in the even semester of the academic year 2012/2013? The form of this research is collaborative classroom action research, in collaborative classroom action research involving teachers, principals, and outsiders in one team simultaneously, with the aim of improving learning outcomes, the development of theory and teacher performance improvement. This team relationship is a partnership, meaning that the position of team members with each other is the same that aims to think about the issues to be studied in classroom action research. In this case the researcher serves as a teacher. Action will be done is in order to improve the results of teaching mathematics at class VD SDN 06 in Perawang Barat. The data in this study were collected with observation sheet and mathematics learning result test. Observations were made to the activities of the students and teachers during the learning process for each meeting by filling out the observation sheets that have been filled in by observing the observation sheets of each teacher and student behavior on the observation sheet. While data is about mathematics learning result collected through daily test (UH1) and daily test (UH2) which contains problem based on indicator that will be achieved based on lattice test result of learning. The data obtained in this research is then analyzed through descriptive analysis.Descriptive data analysis aims to describe data about student learning outcomes on subject matter using in problem solving. Based on the results of research and discussion concluded that the application of direct learning model in groups can improve student learning achievement at VD SDN 06 in Perawang Barat class on the subject matter using fractions in problem solving.